Unveiling the Potential of Virtual Reality in Pakistani Journalism: Insights from an Experimental Study - Naveed Ullah Hashmi, Naveed Ullah Hashmi; Dr. Wajid Zulqarnain,; Amna Zulqarnain, (Journal of Peace, Development and Communication, 2024)
Virtual reality is becoming the potential power of near future to reshape news and journalism. However, this technology has yet to break new grounds in Pakistani media. This study is to investigate the impact of virtual technology on the Pakistani audience, focusing on how media content consumed through VR affects their sense of presence. In this experimental study, quantitative approach has been used. 240 university students of Media Sciences department within twin cities of Pakistan have gone through the experiment. Three groups, each of eighty students have been created, where each group watched VR news videos selected from The New York Times website; one with head-mounted devices (Oculus Quest 2), one on mobile without head-mounted device and one on LED without a head-mounted device. The evaluation of three groups enlightens that the groups with head-mounted device showed significantly higher level of telepresence as compared to group without head-mounted device. Overall, this study has the potential to promote VR technology as a popular concept in Pakistani news media. Also, study findings can be beneficial for organization and media outlets when selecting VR news themes and creating VR content in Pakistan.